2020
DOI: 10.1002/adom.202000720
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Er/O‐Doped Silicon Light‐Emitting Diodes at Communication Wavelength by Deep Cooling

Abstract: A silicon light source at the communication wavelength is the bottleneck for developing monolithically integrated silicon photonics. Doping silicon with erbium and oxygen ions is considered one of the most promising approaches to produce silicon light sources. However, this method suffers from a high concentration of defects in the form of nonradiative recombination centers at the interface between the crystalline silicon and large Er2O3/ErSi1.7 precipitates during the standard rapid thermal treatment. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…13 To overcome these obstacles, the focus has shifted to alternative host materials and/or fabrication methods to develop suitable Si-based matrices with more excitable Er 3+ ions. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…13 To overcome these obstacles, the focus has shifted to alternative host materials and/or fabrication methods to develop suitable Si-based matrices with more excitable Er 3+ ions. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with our recent finding that photoluminescence from the deepcooling-processed samples is two orders of magnitude stronger than the RTA-processed ones. [31] In Figure 3b, the dark current density for both samples first drops exponentially due to the dominance of the exponential terms in Equation ( 2). The current later levels off at lower temperature due to the nonexponential term in Equation ( 2) that is a power function of temperature T. From the exponential dependence, we found that the defect energy levels are located 0.27 and 0.10 eV ( = E t -E v ) above the Si valence band for the DC and RTA processed sample, respectively (see Figure 3b).…”
Section: Resultsmentioning
confidence: 94%
“…[29] The DC processed Er/O doped Si wafer will have a much longer back-transfer time since its photoluminescence efficiency is largely enhanced. [31] The DC processed Er/O doped Si waveguide photodiode may have a back transfer time possibly up to 5 × 10 −6 s, which leads to a cutoff frequency 1 2 1 2 3.14 5 10 30 kHz bt bt 6…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations